The potassium channel GhAKT2bD is regulated by CBL–CIPK calcium signalling complexes and facilitates K+ allocation in cotton. Issue 15 (22nd May 2022) - Zhang, Rui; Dong, Qiuyan; Zhao, Panpan; Eickelkamp, Anna; Ma, Chunmin; He, Gefeng; Li, Fangjun; Wallrad, Lukas; Becker, Tobias; Li, Zhaohu; Kudla, Jörg; Tian, Xiaoli
Abstract : Efficient allocation of the essential nutrient potassium (K + ) is a central determinant of plant ion homeostasis and involves AKT2 K + channels. Here, we characterize four AKT2 K + channels from cotton and report that xylem and phloem expressed GhAKT2bD facilitates K + allocation and that AKT2‐silencing impairs plant growth and development. We uncover kinase activity‐dependent activation of GhAKT2bD‐mediated K + uptake by AtCBL4–GhCIPK1 calcium signalling complexes in HEK293T cells. Moreover, AtCBL4–AtCIPK6 complexes known to convey activation of AtAKT2 in Arabidopsis also activate cotton GhAKT2bD in HEK293T cells. Collectively, these findings reveal an essential role for AKT2 in the source‐sink allocation of K + in cotton and identify GhAKT2bD as subject to complex regulation by CBL–CIPK Ca 2+ sensor–kinase complexes. Abstract : This study characterizes four AKT2 K + channels from cotton and reveals that GhAKT2bD facilitates K + allocation. K + ‐uptake activity of GhAKT2bD is regulated by phosphorylation through CBL4–CIPK calcium signaling complexes. Collectively, this study establishes an essential role for AKT2 in source‐sink allocation of K + in cotton and identifies GhAKT2bD as subject to complex regulation by CBL–CIPK Ca 2+ sensor–kinase complexes.